Transfeminism in Puerto Rico (Periphērica, 2026)
This article offers a brief genealogy of transfeminism in Puerto Rico, tracing its emergence as a coalitional political praxis at the intersection of feminist, queer, and anti‑colonial struggles since the early twenty‑first century. Focusing on student strikes at the University of Puerto Rico, grassroots organizing against austerity and colonial governance, and responses to gender‑based and anti‑trans violence, it argues that transfeminism in Puerto Rico is not a single‑issue identity politics but a materially grounded, intersectional project. The article examines the central role of trans women activists, sex worker–led mutual aid networks, and cultural production in shaping transfeminist world‑making practices, particularly in moments of crisis such as Hurricane María, the summer 2019 uprising, and the COVID‑19 pandemic. Through analysis of activist organizing, artistic interventions, and popular culture, the essay demonstrates how Puerto Rican transfeminism has become a leading force in contemporary struggles against colonialism, racial capitalism, and gender violence.